Synthesis and Characterization of Some New Derivatives From 2-Mercaptobenzoxazole - R. Ahmad, Mohammad; A. Mohsen, Ali (Iraqi Journal of Science, 2023)
In this work 2-mercaptobenzoxazole (2-MBO) (1), was prepared by using homemade Auto clave .The synthesis involve treatment of 2-MBO with 2-chloro acetyl chloride to give 2-chloroacetyl thio benzoxazole (2), the product was treated with phenyl hydrazine to give 2-phenyl hydrazide acetyl thio benzoxazole (3). The new derivatives (4-13) were synthesized by reaction of 2-phenyl hydrazide acetyl thio benzoxazole (3) with different aromatic aldehydes in the presence of acetic acid. The compound (2) was treated with hydrazine hydrate to give product (14) then treated with different aromatic aldehydes in the presence of glacial acetic acid to give Schiff bases derivatives (15-24). Structure of all the prepared compounds confirmation were proved using (FT-IR), (1H-NMR), (13C-NMR) spectra and elemental analysis (C .H .N.S) in addition to melting points.